Challenge and the Characteristics of Teachers in The Interaction of Teaching Quranic Exegesis - Dwi Randa Gunawan; Abd. Kahar (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This article describes the characteristics of teachers in the interaction of teaching Quranic exegesis. The method used in this research is a literature review based on Quranic exegesis books. Data analysis was carried out through the processes of data searching, collection, processing, analysis, and conclusion. Based on the research results, the primary characteristics of a teacher must include a spirit of love and compassion for students, a sincere heart in carrying out their teaching duties, and mastery of various educational science methods. A teacher must prioritize patience and be willing to advise, provide understanding, and remind students who have committed mistakes or transgressions. Hard skills in teacher characteristics include expertise in designing instruction by setting learning targets. Keywords: Teacher Characteristics, interaction, teaching, Quranic exegesis